Using recombinant camel chymosin to make white soft cheese from camel milk - Al-zoreky, Najeeb S.; Almathen, Faisal S. (Food chemistry, 2021)
•Camel milk (CAM) is a complete food.•Rennet enzymes could not coagulate CAM.•Recombinant camel chymosin coagulated CAM.•CAM soft cheeses are added-value products from milk surplus.•Drained whey is rich in nutrients and functional constituents.•Soft cheese and whey of CAM would contribute to food security and sustainability. Bovine derived chymosin in rennet cannot coagulate camel milk (CAM). The study aimed at producing cheese curd from CAM using a recombinant camel chymosin. Pasteurized CAM was prepared for curdling using a recombinant camel chymosin (50 IMCU/ kg). CAM (pH 6.65) contained 2.83% Fat, 3.34% proteins and 9.11% non-fat solids. Physicochemical properties of soft cheese from cultured CAM were 51.89%, 15.62%, 20.21% and 2.47% for moisture, protein, fat and ash, respectively. Cultured CAM afforded higher cheese yield (8.75%) than non-cultured CAM (3.34%). CAM cheese whey had 48.94% and 76.80% of the fat and proteins, respectively, of their corresponding concentrations in CAM. The study is the first report on soft cheeses from CAM (cultured and non-cultured) using a recombinant camel chymosin, with reference to whey constituents. CAM cheese and whey could be added-value products.